Penyuluhan Dan Penanaman Pohon Bagi Masyarakat Sekitar Hutan Di Desa Cikahuripan, Kecamatan Cimanggung, Kabupaten Sumedang Untuk Menjaga Kelestarian Hutan - Dwi Wahyuni; Asep Purwanto; Rian Susila; Prasetyo Widodo; Fahriza Luth (Jurnal Informasi Pengabdian Masyarakat, 2024)
Communities living close to forests can certainly be an important support for sustainable forest management. Their provision of and knowledge about forest sustainability is important as it impacts their lives. For this reason, the academic community of the Faculty of Forestry of Winaya Mukti University in Cikahuripan village conducted information sessions on forest sustainability aimed at changing the living behavior of people around the forest so that the existing forests are conserved and managed sustainably. The extension method used consists of the presentation of materials, discussions and the planting of forest seeds. As part of the community service activities conducted by the Unwim Faculty of Forestry academic community, they work with the people surrounding the forest in Cikahuripan village to protect the forest together by following the importance of the functions of the forest to the local people and obtaining relevant information. In addition, the residents of Cikahuripan village are willing to participate in the conservation of the forest by planting 300 seeds of acacia, mahogany, meranti and sengon forest plants.